PSYCHOLOGICAL ASPECTS OF PROFESSIONAL PRIMARY CLASS TEACHER TRAINING - Z.M. Miroshnyk (Academy of Cognitive and Natural Sciences, 2001)
Professional training of a primary school teacher is considered to he many-sided. This article touches upon psychological aspects of this problem. Analyzing the main conditions for development of a teacher as a professional the authors stresses on the following: personal orientation on a concrete pupil, psychological competence and self-management of a primary class teacher.